Pancreatic exocrine insufficiency after pancreatic resection: a systematic review - Marcello Di Martino; Ángela de la Hoz Rodriguez; Andrea Saibanti; Guillermo Salvador Camarmo; Nico Pagano; Elena Martín-Pérez; Matteo Donadon (BMC Surgery)
Abstract Introduction Pancreatic exocrine insufficiency (PEI) is a condition defined by a reduction in pancreatic exocrine activity that impairs normal digestion. Despite established guidelines recommendations, precise diagnosis of PEI after pancreatic resection are infrequently achieved. This review aims to provide a comprehensive overview of the methodology and accuracy of diagnostic tools available for evaluating PEI after pancreatic resection. Methods A review of PEI diagnostic tests was conducted using a combined text and MeSH search strategy to identify relevant articles focused on post-pancreatectomy PEI diagnosis. Results The literature search yielded 4,874 records, and 30 studies were included in the analysis, with a total of 2,305 patients. The reported frequency of PEI across the included studies varied widely, though more than two-thirds of included papers reported an incidence of PEI above 65% in patients who underwent pancreatoduodenectomy or distal pancreatectomy. The faecal elastase-1 (FE-1) test was the most frequently used test for diagnosing post-pancreatectomy PEI. Six studies compared the diagnostic accuracy of FE-1 with faecal fat tests or 13 C breath tests, finding no significant differences. Five studies reported on micronutrient deficiencies. Conclusion The FE-1 test is the most commonly used diagnostic tool for post-pancreatectomy PEI; however, well-designed studies comparing the diagnostic accuracy of various tests for PEI are lacking. Additionally, few studies report on micronutrient deficiencies, variations in anthropometric data or PEI-related patient-reported outcomes. Future studies should aim to establish a gold standard for diagnosis and severity assessment of post-pancreatectomy PEI and provide guidance for tailored pancreatic enzyme replacement therapy.